The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1177/0091270006297227
|View full text |Cite
|
Sign up to set email alerts
|

Anidulafungin Does Not Require Dosage Adjustment in Subjects With Varying Degrees of Hepatic or Renal Impairment

Abstract: Two open-label studies assessed the effects of hepatic and renal impairment on anidulafungin pharmacokinetics. A single 50-mg dose was administered intravenously to subjects with varying degrees of hepatic or renal insufficiency or with end-stage renal disease; all were matched to normal healthy controls. Anidulafungin was well tolerated. AUC, CL, C(max), t(max), t(1/2), and V(ss) between renally impaired subjects and controls were not significantly different (P>.05), and no measurable amounts of drug were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
70
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 15 publications
10
70
0
3
Order By: Relevance
“…Our results confirm previous reports that exposure in ICU patients is lower than that in healthy volunteers (11,12). Three studies, including ours, found lower exposures in ICU patients than in other reference cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm previous reports that exposure in ICU patients is lower than that in healthy volunteers (11,12). Three studies, including ours, found lower exposures in ICU patients than in other reference cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, intact parent drug, as well as metabolites, appear to be eliminated via biliary excretion, without involvement of the kidneys. The conclusion that anidulafungin is not a substrate for phase 1 and phase 2 metabolic pathways is strongly supported by the results of our in vitro metabolism studies and is further substantiated by previous reports indicating that hepatic impairment, regardless of severity, does not increase the systemic exposure to anidulafungin (6).…”
Section: Discussionsupporting
confidence: 89%
“…Due to the difficulty in obtaining a stable degradation product(s) of anidulafungin, similar experiments assessing the potential action of drug transport proteins on these metabolites have not been conducted to date, and the exact nature of the biliary excretion of the degradation products, therefore, remains unclear. The assumed lack of renal and hepatic involvement in the elimination of anidulafungin is also supported by pharmacokinetic studies in renal or hepatic impairment subjects (6). These studies indicated that the pharmacokinetics of anidulafungin were not significantly affected by impaired renal or hepatic function, regardless of severity, and suggested that dose adjustment of anidulafungin is not necessary in these patient populations.…”
Section: Discussionmentioning
confidence: 82%
“…Although the three echinocandins are from the same class, differences in the route of metabolism, the requirement for a loading dose, dose adjustments in patients with moderate-to-severe hepatic disease, and the dosing schedules for different types of Candida infections exist (9). As no dose adjustment of anidulafungin is required for patients with renal/ hepatic impairment and no clinically relevant drug-drug interactions are known (10,11), anidulafungin might be a particularly valuable treatment option in ICU patients. So far, no studies have formally evaluated the pharmacokinetic profile of anidulafungin in critically ill patients.…”
mentioning
confidence: 99%